Solve for F
F = \frac{76231633877289}{4543760} = 16777213\frac{4536409}{4543760} \approx 16777213.998382177
Assign F
F≔\frac{76231633877289}{4543760}
Share
Copied to clipboard
F=\left(\frac{1}{65536}-1\right)^{-1}+\left(25^{-2}-1\right)^{-1}+\left(64^{-3-1}\right)^{-1}
Calculate 16 to the power of -4 and get \frac{1}{65536}.
F=\left(-\frac{65535}{65536}\right)^{-1}+\left(25^{-2}-1\right)^{-1}+\left(64^{-3-1}\right)^{-1}
Subtract 1 from \frac{1}{65536} to get -\frac{65535}{65536}.
F=-\frac{65536}{65535}+\left(25^{-2}-1\right)^{-1}+\left(64^{-3-1}\right)^{-1}
Calculate -\frac{65535}{65536} to the power of -1 and get -\frac{65536}{65535}.
F=-\frac{65536}{65535}+\left(\frac{1}{625}-1\right)^{-1}+\left(64^{-3-1}\right)^{-1}
Calculate 25 to the power of -2 and get \frac{1}{625}.
F=-\frac{65536}{65535}+\left(-\frac{624}{625}\right)^{-1}+\left(64^{-3-1}\right)^{-1}
Subtract 1 from \frac{1}{625} to get -\frac{624}{625}.
F=-\frac{65536}{65535}-\frac{625}{624}+\left(64^{-3-1}\right)^{-1}
Calculate -\frac{624}{625} to the power of -1 and get -\frac{625}{624}.
F=-\frac{9094871}{4543760}+\left(64^{-3-1}\right)^{-1}
Subtract \frac{625}{624} from -\frac{65536}{65535} to get -\frac{9094871}{4543760}.
F=-\frac{9094871}{4543760}+\left(64^{-4}\right)^{-1}
Subtract 1 from -3 to get -4.
F=-\frac{9094871}{4543760}+\left(\frac{1}{16777216}\right)^{-1}
Calculate 64 to the power of -4 and get \frac{1}{16777216}.
F=-\frac{9094871}{4543760}+16777216
Calculate \frac{1}{16777216} to the power of -1 and get 16777216.
F=\frac{76231633877289}{4543760}
Add -\frac{9094871}{4543760} and 16777216 to get \frac{76231633877289}{4543760}.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}